Clinician Emotions Surrounding Pediatric Oncology Patient Deterioration - Graetz, Dylan E.; Giannars, Emily; Kaye, Erica C.; Garza, Marcela; Ferrara, Gia; Rodriguez, Mario; Soberanis Vasquez, Dora Judith; Mendez Aceituno, Alejandra; Antillon-Klussmann, Federico; Gattuso, Jami S.; Andes, Karen L.; Mandrell, Belinda N.; et al. (Frontiers in Oncology, 2021)
BACKGROUND: Pediatric oncology patients have a high rate of clinical deterioration frequently requiring critical care. Patient deterioration events are distressing for clinicians, but little is known about how Pediatric Early Warning Systems (PEWS) impact clinicians’ emotional responses to deterioration events. METHODS: Semi-structured interviews were conducted with 83 nurses, pediatricians, oncologists, and intensive care clinicians who had recently participated in a patient deterioration event at two pediatric oncology hospitals of different resource-levels: St. Jude Children’s Research Hospital (N=42 participants) in Memphis, Tennessee or Unidad Nacional de Oncología Pediátrica (N=41 participants) in Guatemala City, Guatemala. Interviews were conducted in the participants’ native language (English or Spanish), transcribed, and translated into English. Each transcript was coded by two researchers and analyzed for thematic content. RESULTS: Emotions around patient deterioration including concern, fear, and frustration, were reported across all disciplines at both hospitals. Concern was often triggered by an elevated PEWS score and usually resulted in increased attention, which in turn reassured bedside clinicians that patients were receiving necessary interventions. However, persistently elevated PEWS scores, particularly at St. Jude Children’s Research Hospital, occasionally resulted in a false sense of relief, diminishing clinician attention and negatively impacting patient care. Nurses at both institutions described how PEWS amplified their voices, engendering confidence and empowerment, two of the only positive emotions described in the study. CONCLUSION: Clinicians experienced a range of emotions while caring for high-risk patients in the setting of clinical deterioration. These emotions have the potential to contribute to compassion fatigue and burnout, or to resilience. Acknowledgement and further investigation of the complex interplay between PEWS and clinician emotions is necessary to maximize the impact of PEWS on patient safety while simultaneously supporting staff wellbeing.